The Role of Financial Technology Adoption on Financial Inclusion among Unbanked Populations - Nahwan, Darwin (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The level of financial inclusion in Indonesia continues to increase, but there is still a gap between urban and rural areas. Unbanked groups such as informal entrepreneurs and women in the suburbs face barriers to accessing formal financial services. Although financial technology is growing rapidly, its adoption among low-income earners is still hampered by infrastructure, cost, and digital literacy factors. This study aims to analyze the driving and inhibiting factors of financial technology adoption by unbanked groups from a development economics perspective. The study used a mixed methods approach, with a focus on quantitative surveys on 100 respondents and qualitative interviews on 10 key informants. Data analysis includes logistic regression to measure the influence of socio-economic variables and thematic coding to uncover risk perceptions and cultural barriers to Financial Technology adoption. This study shows that financial technology adoption is influenced by socio-economic factors such as age, type of business, and income. MSMEs in the food sector are 4.5 times more likely to adopt financial technology than households due to the need for efficiency and microtransactions. Expanding financial inclusion requires collaboration among government, service providers, and communities to strengthen infrastructure and build trust.